Status of inflammation among negritos and Malays with Metabolic Syndrome / Noor Mohd Firdaus Othman - Othman, Noor Mohd Firdaus (2019)
Objective: To determine metabolic syndrome components with inflammatory biomarker among Negritos compared with Malays. Method: 600 subjects (150 Negritos, 450 Malays) were recruited in this cross-sectional study. 127 subjects (21 Negritos, 106 Malays) were diagnosed with MS while 473 were non-MS (129 Negritos, 344 Malays). The groups were matched for age and gender. Serum samples were collected for analysis of biomarkers of inflammation [high-sensitivity C-reactive protein (hsCRP)]. Result: Amongst the Malays and Negritos, MS subjects had higher hsCRP (p<0.05) than their non-MS counterpart. High incidences of low HDL-c levels were observed in Negritos but none was detected among the Malays. Conclusion: MS is associated with enhanced inflammation, endothelial activation and pro- thrombogenesis. Orang Asli staying in the inlands are predisposed to cardiovascular diseases. The perception of Orang Asli being healthier than the urban people no longer holds. Inherent genetic background may contribute to the increased risk of coronary artery disease.